Perlindungan Hukum Bagi Pemenang Lelang Atas Objek Hak Tanggungan Berdasarkan Studi Putusan Nomor: 361/Pdt/2017/PT.SMG - Wibowo, Fitri Mustikaning; Widodo, Selamat (Fakultas Hukum Universitas Islam Batik Surakarta, 2024)
Abstract Indonesia recognize two collateral institutions that can be used by the public, namely pawn and mortgage based on the Civil Code.The development of law in Indonesia then introduced two new collateral institutions, namely mortgage and fiduciary rights. Mortgage rights are security institutions that can be used on objects in the form of land rights. The practice of implementing the execution of the object of mortgage rights collateral that has become the right of the auction winner generally still experiences many obstacles. This research aims to find out and analyse the legal protection for the winner of the auction along with the arrangement of the execution of the auction object which is still controlled by the giver of the mortgage. This research is writtenusing the normative juridical method, namely using the law, and journals relevant to this research. This research describes the legal protection of auction winners who are in good faith over the object of mortgage rights, so that even though the object of mortgage rights is still controlled by the debtor or other parties, the auction winner can still control the auction object by fulfilling the auction requirements and procedures and submitting an application for execution correctly.